Pagina de inicio
/
Matemáticas
/
2sqrt (18)-sqrt (27)-sqrt (50) Simplify the expression: 2surd -59 -2sqrt (2)-3sqrt (3) sqrt (2)-3sqrt (3) -3.782

Problemas

2sqrt (18)-sqrt (27)-sqrt (50)
Simplify the expression:
2surd -59
-2sqrt (2)-3sqrt (3)
sqrt (2)-3sqrt (3)
-3.782

2sqrt (18)-sqrt (27)-sqrt (50) Simplify the expression: 2surd -59 -2sqrt (2)-3sqrt (3) sqrt (2)-3sqrt (3) -3.782

Solución

avatar
Carolinaprofessionell · Tutor durante 6 años
expert verifiedVerificación de expertos
4.6 (146 votos)

Responder

To simplify the expression \(2\sqrt{18} - \sqrt{27} - \sqrt{50}\), we first need to simplify each square root term individually.<br /><br />1. Simplify \(\sqrt{18}\):<br /> \[<br /> \sqrt{18} = \sqrt{9 \times 2} = \sqrt{9} \times \sqrt{2} = 3\sqrt{2}<br /> \]<br /><br />2. Simplify \(\sqrt{27}\):<br /> \[<br /> \sqrt{27} = \sqrt{9 \times 3} = \sqrt{9} \times \sqrt{3} = 3\sqrt{3}<br /> \]<br /><br />3. Simplify \(\sqrt{50}\):<br /> \[<br /> \sqrt{50} = \sqrt{25 \times 2} = \sqrt{25} \times \sqrt{2} = 5\sqrt{2}<br /> \]<br /><br />Now substitute these simplified forms back into the original expression:<br />\[<br />2\sqrt{18} - \sqrt{27} - \sqrt{50} = 2(3\sqrt{2}) - 3\sqrt{3} - 5\sqrt{2}<br />\]<br /><br />Simplify the expression:<br />\[<br />= 6\sqrt{2} - 3\sqrt{3} - 5\sqrt{2}<br />\]<br /><br />Combine like terms:<br />\[<br />= (6\sqrt{2} - 5\sqrt{2}) - 3\sqrt{3} = \sqrt{2} - 3\sqrt{3}<br />\]<br /><br />So, the simplified form of the expression is:<br />\[<br />\sqrt{2} - 3\sqrt{3}<br />\]<br /><br />Therefore, the correct answer is:<br />\[<br />\sqrt{2} - 3\sqrt{3}<br />\]
Haz clic para calificar: